Cannabis stocks returns: The role of liquidity and investors' attention via google metrics - Stephanos Papadamou; Alexandros Koulis; Constantinos Kyriakopoulos; Athanasios P. Fassas (International Journal of Financial Studies, 2022)
This paper studies one of the most popular investment themes over recent years, investing in the cannabis industry. In particular, it investigates relationships between investor attention, as proxied by Google Trends, and stock market activities, i.e., return, volatility, and liquidity. To this end, in the empirical analysis we study how liquidity and investors' attention affect the return dynamics of an investment in cannabis stocks by augmenting the three-factor Fama-French model. In addition, we use a vector autoregressive approach and the impulse response function to measure shock transmission between the variables under consideration. Our empirical findings show that there is a statistically positive relationship between cannabis stock returns and liquidity. We also find that increased investors' attention results in higher returns.
Keywords: 330; cannabis stocks; Google metrics; investors' attention; liquidity